Intervención optométrica en paciente masculino de 27 años con exceso acomodativo. - Tejada Alvarado, Santiago Stiven (2024)
The accommodative excess is a visual condition in which an excessive contraction of the ciliary muscle is perceived, which causes the eye to present problems to relax and focus on objects that are at a far distance after straining the vision at short distances. This project considers the clinical case of a 27 year old patient, who reports presenting common symptoms related to this deficiency such as recurrent headaches, visual fatigue and blurred vision. For the definitive diagnosis of the condition, a series of optometric evaluations were performed, which supported the measurement of flexibility, amplitude, accommodative posture, among others. The results obtained showed a relevant decrease in the relaxation capacity of the eye, corroborating the diagnosis of accommodative excess. The proposed plan to treat this patient involved the prescription of glasses to relieve accommodative strain and the design of an optical therapy routine focused on improving flexibility. At the same time, changes in the patient's routine such as frequent breaks during digital screen use were suggested to prevent aggravation of the repercussions. In this clinical case, the development of an accurate diagnosis and the design of an appropriate treatment for the accommodative excess is imperative. The importance of continuing education and clinical practice in the development of professional competencies in optometry is also emphasized.